Empiric antifungal therapy in patients with cutaneous and subcutaneous phaeohyphomycosis. Issue 5 (25th February 2022) - Noguchi, Hiromitsu; Matsumoto, Tadahiko; Kimura, Utako; Hiruma, Masataro; Kano, Rui; Yaguchi, Takashi; Kubo, Masahide; Kashiwada‐Nakamura, Kayo; Fukushima, Satoshi
Abstract: We encountered two cases of phaeohyphomycosis caused by Exophiala jeanselmei and E. oligosperma that were treated with fosravuconazole and terbinafine, respectively. Our cases were successfully treated with empiric therapy before the pathogen's species or antifungal sensitivity had been determined. We summarized 32 cases of cutaneous and subcutaneous phaeohyphomycosis caused by Exophiala species in Japan. The patients received antifungals, including itraconazole, terbinafine, voriconazole, and fosravuconazole, and the treatment success rates of these monotherapies were 77% (17/22), 67% (8/12), 100% (5/5), and 50% (1/2), respectively. Although the broad‐spectrum azole antifungal itraconazole is the first choice for treatment, terbinafine at 125 mg/day might exert the same efficacy. Fosravuconazole is a novel broad‐spectrum azole and a moderate inhibitor of Cyp3A4 that causes fewer drug interactions than itraconazole and voriconazole, indicating a promising drug for this disease.